Internal State Language and Emotion Understanding in Children Attending Mental Health Services - SHERIDAN, AUDREY CHRISTINA (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2019)
Thesis Title: Internal State Language and Emotion Understanding in Children Attending Mental Health Services. Parental use of internal state (mental state) language (ISL) has been linked with children s understanding of emotion in the preschool period but it is not known if this association extends into middle childhood or if associations between these constructs are found among children with emotional and behavioural difficulties (EBD) and their parents. Furthermore, there is evidence that children with EBD may have difficulty understanding emotions yet there is little research on factors contributing to emotion understanding among this group. The present study examined associations between parent ISL and children s emotion understanding (EU) among a group of children attending mental health services for difficulties with EBD and a matched control group from the community. Twenty referred children and parents who attended clinical services for EBD and forty control group children and parents from the community were visited in the family home and measures of emotion understanding were administered. Parent-child conversation was recorded, transcribed and analysed for use of ISL. Three different measures of EU were examined; the Emotion Vocabulary Test (EVT, Dyck, 2012); the Test of Emotion Comprehension (Pons, Harris & de Rosnay, 2004) and the Fluid Emotions Test (FET, Dyck, 2012). The study found that parent ISL during book reading was significantly associated with boys abilities on emotion vocabulary and the size of the effect was in the small to medium range. Parent ISL was also linked to FET scores for children in the community group and the effect size was in the medium range. The strength of the associations increased when child intellectual ability and parent education were controlled. Children s expressive language and attention predicted EU abilities. Attention difficulties were associated with quicker response times and greater errors in naming happy and surprised emotion expressions. Expressive language difficulty was associated with poorer emotion vocabulary. The results indicate that children s ability to pay attention and their expressive vocabulary may be more important in understanding emotion than group membership or overall EBD symptoms. The findings suggest that both parent ISL and child characteristics are important for children s EU skills in mid-to-late childhood. The focus on parent ISL and child EU in an older, participant group is a novel approach that may benefit from replication. The research supports the social constructionist view that discussing mental states may continue to be an important mechanism of emotion socialization among this age group. Despite few overall group differences in EU abilities, differences in the strength of associations between EU skills and child abilities in the target group versus the control group highlighted the importance of studying a clinical participant group for revealing important correlates of the construct of EU. The study findings have practical application in clinical settings by highlighting the importance of expressive language and attention skills in EU among children with EBD.
APPROVED
Keywords: Emotion Understanding; Emotion Recognition; Mental State Talk; Emotional and Behavioural Difficulties; Parent Internal State Language